THE EFFECT OF USING THINK PAIR SHARE (TPS) MODELON STUDENT’S IN WRITING DESCRIPTIVE TEXT ABILITY (A Study at the Tenth Grade Students of SMA Negeri 1 Pinangsori 2018/2019 Academic Year) - nia daniati zebua (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract:The purpose of this research are to find out : 1) the extent of students’ achievement in writing descriptive text taught by using Think Pair Share model at the Tenth Grade Students of SMANegeri1 Pinangsori, 2) the extent of students’ achievement in writing descriptive text taught by using Think Pair Share model at the tenth Grade Students of SMANegeri1 Pinangsori, 3) whether there is a significant comparison study of the students’ in writing descriptive text taught by using model think pair share at the Tenth Grade Students of SMANegeri1 Pinangsori. The population of this research is all of the Eighth Grade Students of SMA Negeri 2 Pinangsori consist of 308 students. The sample was 30 respondents to the experimental class and 30 respondents to the control class which were taken by think pair share . Because the research is conducted to find out the cause effect relationship and to compare the treatments, the research method used is experimental method. Then, the data is collected by using the instrument. The instrument used are rearrangement and fill in the blank test.The hypothesis of this research is there is a significant comparison study of the students’ in writing descriptive text taught before and after by using think pair share the Tenth Grade Students of SMA Negeri 1 Pinangsori.The calculation of ttest formula is higher than score of “t” table. Means, the score of the ttest is 6,17 meanwhile the sore of the ttable is 2,04 at 5% significant level with the effect of using model think pair share (df) 29(ttest6,17>ttable 2,04) and hypothesis accepted. It means that there is a significant effect of model think pair share in writing descriptive text ability at tenth grade students of SMA Negeri 1 pinangsori. Keywords :Thik Pair ShareModel, Writing Ability.